Geochemical classification and secondary alteration of crude oil in the southern thrust belt of Junggar Basin - Qin, Zhijun; Qi, Hongyan; Liang, Zeliang; Ma, Wanyun; Wang, Ruiju; Wu, Wei’an (Frontiers in Earth Science, 2023)
This study analyzed, 18 oil samples from four representative oil-bearing secondary tectonic units in the southern thrust belt of the Junggar Basin. The genetic types and the secondary alteration of oil were discussed based on the characteristics of light hydrocarbon compounds, adamantanes, sterane/terpene biomarkers, and stable carbon isotopic composition of the bulk oil. . The results show that the oil in the study area can be divided into five categories. Type I oil is characterized by 13C-depleted carbon isotopes, a low pristane to phytane ratio, and high gammacerane and low diasterane content, whereas Type II oil exhibits the opposite characteristics. Type III is very similar to Type II oil but has a higher 13C-depleted bulk carbon isotopic composition and a wider carbon number of tricyclic terpenes. Type IV and V oils are similar to Type I oils, except for relatively lower gammacerane content. Further, Type IV oils also have high ααα 20R regular sterane content, 13C-enriched bulk oil carbon isotopes, and a higher pristane to phytane ratio than Type I oil. In contrast, the relative content of C27 regular steranes of Type V oils is considerably lower than that of Type I oils. The oil in the study area has not suffered from biodegradation. Maturity information indicated by regular biomarkers (i.e., steroid, terpene, and phenanthrene) and adamantane differs significantly, with the latter exhibiting a strong cracking characteristic. This reflects the charging and mixing of oils formed at different evolution stages. The other types of oils are in the normal oil-generating window and do not suffer from intense cracking. The oil in the study area is generally subjected to evaporative fractionation, but there are obvious differences in the degree of alteration between different oil-bearing structures and different reservoirs with the same structure. This study is of great significance for understanding the origin and accumulation process of oil and gas in a complex structural zone.